Recurrent primary mesenteric liposarcoma - Malla, Srijan; Rayamajhi, Jyoti; Rawal, Sushil Bahadur; Giri, Naresh Kumar (Medical Journal of Shree Birendra Hospital, 2012)
Liposarcoma occurring in the mesentery primarily is a rare entity, scarcely reported in world literature. Here, we report one such case that recurred thrice in spite of complete resection and adjuvant therapy. A literature review on the management of such an aggressive tumor is also outlined. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6460 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 29-31